Role of phosphodiesterase-3 inhibitor in cardiorespiratory fitness and functional class of patients with pulmonary hypertension: A randomized, double-blind, placebo-controlled trial - Sofia, Sefri N.; Bahrudin, Udin; Uddin, Ilham; Sobirin, Muhammad A.; Setiawati, Erna; Hardiningsih, Galuh; Tjandra, Kevin C.; Limijadi, Edward KS. (Narra J, 2025)
Many patients with acyanotic shunt congenital heart disease (CHD) are diagnosed only in adulthood, by which time pulmonary hypertension (PH) has developed, impairing their functional class and cardiorespiratory fitness. While PH treatments are limited and expensive, cilostazol, a phosphodiesterase-3 inhibitor, has shown potential in reducing pulmonary artery pressure and improving heart function, offering hope for better patient outcomes. The aim of this study was to evaluate the effects of cilostazol on cardiorespiratory fitness and functional class in patients with acyanotic shunt CHD with PH using a randomized, double-blind, placebo-controlled trial. The trial was conducted at Dr. Kariadi Hospital, Semarang, Indonesia, from March 2022 to March 2023. Patients aged 14–75 years were randomly assigned to receive cilostazol (initially 200 mg, later adjusted to 100 mg) or placebo for three months. Cardiorespiratory fitness was assessed using the six-minute walk test (6MWT) and VO2 max at pre-intervention and three months post-intervention. After three months, the mean 6MWT was not significantly different between cilostazol and placebo groups (319.65±50.52 vs 317.65±45.26 meters; p=0.090). Similarly, the VO2 max was also not significantly different between cilostazol and placebo groups (10.74±2.59 mL/kg/min vs 10.73±2.8 mL/kg; p=0.099). However, the percentage of patients who had functional class improvement was significantly higher in the cilostazol group compared to the placebo group (90% vs 30%; p<0.001). This study indicated that cilostazol could improve functional class in acyanotic shunt CHD patients with PH. However, larger and more robust trials are warranted to confirm the potential benefits of cilostazol in this patient population.